Culture and psychopathology: An attempt at reconsidering the role of social learning. (26th October 2022) - Fonagy, Peter; Campbell, Chloe; Constantinou, Matthew; Higgitt, Anna; Allison, Elizabeth; Luyten, Patrick
Abstract: This paper proposes a model for developmental psychopathology that is informed by recent research suggestive of a single model of mental health disorder (the p factor) and seeks to integrate the role of the wider social and cultural environment into our model, which has previously been more narrowly focused on the role of the immediate caregiving context. Informed by recently emerging thinking on the social and culturally driven nature of human cognitive development, the ways in which humans are primed to learn and communicate culture, and a mentalizing perspective on the highly intersubjective nature of our capacity for affect regulation and social functioning, we set out a cultural-developmental approach to psychopathology.